Problems of Regulation of Gratification in Law Number 20 Of 2001 Concerning Amendments to Law Number 31 Of 1999 Concerning Eradication of Gratification Criminal Act of Corruption - Tantri Riyadi; Firdiawanti Firdiawanti; Toha Wangse (Rechtsnormen: Journal of Law, 2025)
Background. This research aims to address the problem of regulating gratification in Article 12c of Law Number 20 of 2001. This provision provides the opportunity for state administrators to report gratuities within 30 days. Purpose. However, in its implementation, various problems still arise, both normatively, both practically and legally.   Method. From a normative perspective, Article 12c does not explicitly explain what is meant by "30 working days", does not provide a repair mechanism for late reports, and has the potential to lead to criminalization of administrative matters making it difficult for this rule to run optimally. Results. In practice, many state officials still lack a comprehensive understanding of the obligation to report gratuities. Lack of public awareness and various administrative obstacles in the reporting process exacerbate the situation. Conclusion. As a result, the 30-day grace period is often not implemented properly and creates legal uncertainty. Therefore, the provisions in Article 12c need to be reviewed.